2003
DOI: 10.1074/jbc.m309986200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor (PDGF) Receptor-α-activated c-Jun NH2-terminal Kinase-1 Is Critical for PDGF-induced p21 Promoter Activity Independent of p53

Abstract: Platelet-derived growth factor (PDGF) is a potent mitogen for mesenchymal cells. PDGF AA functions as a "competent factor" that stimulates cell cycle entry but requires additional (progression) factors in serum to transit the cell cycle beyond the G 1 /S checkpoint. Unlike PDGF AA, PDGF B-chain (c-sis) homodimer (PDGF BB) and its viral counterpart v-sis can serve as both competent and progression factors. PDGF BB activates ␣-and ␤-receptor subunits (␣-PDGFR and ␤-PDGFR) and induces phenotypic transformation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
3
28
2
1
Order By: Relevance
“…To obtain genetic evidence for a potential crucial function of PDGF, interference with PDGF signalling was achieved through bicistronic expression of a dn mutant of the PDGF-a receptor (Yu et al, 2000) and red fluorescent protein (RFP) in MIM-R hepatocytes (Figure 7c). The functionality of the dn construct in inhibiting the signalling of PDGF-a receptor has already been tested and verified in a variety of cell lines (Yu et al, 2000(Yu et al, , 2003. The resulting cells, termed MIM-RPDGFdn, were enriched in only about 80% RFP-positive cells even after two rounds of cell sorting, and showed proliferation kinetics comparable to those of MIM-R hepatocytes in vitro (Figure 7b and data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…To obtain genetic evidence for a potential crucial function of PDGF, interference with PDGF signalling was achieved through bicistronic expression of a dn mutant of the PDGF-a receptor (Yu et al, 2000) and red fluorescent protein (RFP) in MIM-R hepatocytes (Figure 7c). The functionality of the dn construct in inhibiting the signalling of PDGF-a receptor has already been tested and verified in a variety of cell lines (Yu et al, 2000(Yu et al, , 2003. The resulting cells, termed MIM-RPDGFdn, were enriched in only about 80% RFP-positive cells even after two rounds of cell sorting, and showed proliferation kinetics comparable to those of MIM-R hepatocytes in vitro (Figure 7b and data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…Among the several kinases that have been described to phosphorylate APP at T668 (Suzuki et al, 1994;Aplin et al, 1996;Iijima et al, 2000;Taru and Suzuki, 2004;Kimberly et al, 2005), the c-Jun NH 2 -terminal kinase (JNK) seems to play an important role in vivo (Kimberly et al, 2005). JNK is a serine/threonine kinase, but it may be activated by pathways involving receptor tyrosine kinases, e.g., the PDGFR (Yu et al, 2003) and c-Kit (Hong et al, 2004), which can be inhibited by Gleevec. Binding of the adaptor protein Fe65 may be regulated by phosphorylation of APP at T668 (Ando et al, 2001;Kimberly et al, 2005), and it has been implicated in AICD stabilization (Kimberly et al, 2001(Kimberly et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PDGF-R␣ is somehow more complex because it triggers inducing signals and inhibitory signals. 14,16 We previously showed, both in vitro and in vivo, that FGF-2 and PDGF-BB interact with high affinity, 14 leading to reciprocal inhibitory effects mediated, at least in part, by PDFG-R␣ and FGF-R1. 13,34 These data represent the first evidence indicating that PDGF-BB may acquire in vivo antiangiogenic effects mediated by PDGF-R␣ and highlight that PDGF activity may be controlled or even counteracted by the expression levels and activation state of the corresponding ␣ and ␤ receptors.…”
Section: Fret Confocal Analysismentioning
confidence: 99%
“…13 Consistent with these data, other groups have shown that PDGF-R␣ may activate positive and negative signals 15 mediated by JNK-1 and p21WAF/CIP1 promoter induction. 16 In the present study, we investigated how HUVECs respond in vitro to a FGF-2/PDGF-BB mixture compared with FGF-2 alone, and we identified a novel controlling mechanism involving FGF-R1/ PDGF-R␣ heterodimerization.…”
Section: Introductionmentioning
confidence: 99%